Español Meanings about the environment for adolescents from the town center of Chala Nueva -Concepción - Macha Guerra, Luz Maria (2024)
The objective of the research was to identify the meaning that the environment has for the adolescents of the Chala Nueva Population Center - Concepción - 2023, the geographical space of the highland area of ​​Canipaco, is characterized by the presence of collectives or human groups in the spaces rural; The rural family brings together nuclear and basically extended households, in the family system, pubescent children and adolescents with rural experience share with their parents, siblings, grandparents, uncles; among neighbors, friends, fellow citizens certain appreciations about the climate, microclimates, the development of genuine wild flora and fauna, that is, the rural ecosystem. The qualitative study, with an ethnographic design, collects information on the meaning that adolescents have about the environment. 10 adolescents of both sexes with rural experience were identified, who will be approached with an in-depth interview guide. The findings show that the environment for the students of the town of Chala Nueva is associated with life, access to oxygen, breathing, access to health, food, quality of life, preserving and promoting flora and fauna. It is concluded that the adolescent with rural experience possesses and executes meanings about the environment, associates and interrelates with life, future and responsibility; the community, the municipality, the health center and the educational centers contributing to this purpose.